2004
DOI: 10.1111/j.1440-1746.2004.03448.x
|View full text |Cite
|
Sign up to set email alerts
|

Argon plasma coagulation as first‐line treatment for chronic radiation proctopathy

Abstract: These results suggest that argon plasma coagulation is a safe and effective modality in the treatment of chronic radiation proctopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 24 publications
3
58
0
5
Order By: Relevance
“…18 Second, local treatment of rectal bleeding is quite successful, especially with argon plasma coagulation. 19 Prevalence of fecal incontinence after radiation therapy showed evidence of progressive worsening of the anorectal function. Yeoh et al 20 found a decline in rectal compliance and thickening of the external anal sphincter in patients after radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…18 Second, local treatment of rectal bleeding is quite successful, especially with argon plasma coagulation. 19 Prevalence of fecal incontinence after radiation therapy showed evidence of progressive worsening of the anorectal function. Yeoh et al 20 found a decline in rectal compliance and thickening of the external anal sphincter in patients after radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…86 In several other studies, cessation of bleeding was reported after 1 to 3 sessions of APC. [87][88][89][90][91][92] Complications of APC include rectal pain, rectal stenosis, altered bowel habits, and rectal wall injury. Reported rates of rectal ulceration leading to fistula development range from <1% to 2%.…”
Section: Argon Plasma Coagulationmentioning
confidence: 99%
“…All patients had rectal bleeding due to CRP (grade 4 in Chutkan scale) (18) and all underwent full colonoscopy examination to rule out other causes of bleeding (i.e. local tumor activity or diverticulosis).…”
Section: Methodsmentioning
confidence: 99%